2022
DOI: 10.54905/disssi/v26i129/ms498e2583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oral hygiene practice during active orthodontic treatment in Saudi Arabia

Abstract: Background: Good oral hygiene is a critical factor to ensure good orthodontic treatment. Maintaining good oral hygiene in orthodontics is one of the essential factors related to compliance. Assessment of oral hygiene practices is crucial for adequate understanding of the patients' oral healthcare need, which may influence the quality and timing of the therapy. Methods: This is an epidemiological study based on electronic survey questionnaire. This research was performed among active orthodontic patients in Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[10,11] Nonetheless, supporting preventive oral hygiene measures through long-term treatment necessitates patient compliance. Unfortunately, several studies have demonstrated poor oral hygiene compliance among orthodontic patients [12][13][14] with a rapid drop in patients' compliance after bonding the orthodontic appliance. [15] Compliance with therapeutic regimens is shaped by many factors including the relationship between the patient and the provider, the perception of disease susceptibility, the perceived benefits of the treatment, and the complexity and duration of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Nonetheless, supporting preventive oral hygiene measures through long-term treatment necessitates patient compliance. Unfortunately, several studies have demonstrated poor oral hygiene compliance among orthodontic patients [12][13][14] with a rapid drop in patients' compliance after bonding the orthodontic appliance. [15] Compliance with therapeutic regimens is shaped by many factors including the relationship between the patient and the provider, the perception of disease susceptibility, the perceived benefits of the treatment, and the complexity and duration of the treatment.…”
Section: Introductionmentioning
confidence: 99%